POLA PENGEMBANGAN AGROINDUSTRI YANG BERDAYA SAING (Studi Kasus Kabupaten Malang) - Fajar Wahyu Prianto (Jurnal Ekonomi Akuntansi dan Manajemen, 2011)
This paper searchs the patternof agricultural competitivenessand its important variables that may influence on agroindustrial growth. Agriculture sector need to developed by industrialization that based on sectoral and spatial competitiveness. The competitiveness can reflected by natural capacity, and industrial efficiency that taken by economic of scale and agglomeration benefits. So, clusterization and industrial linkage will affect to increasing of agroindustrial competitiveness. By using location-quotient index, dynamic shift-share, principle component anaylisis, and cluster analysis, the result shows that most of farm and dairy products has competitiveness. They need an incentive instruments that can provide all of agroindustrial growth. Keywords: agricultural, dynamic shift-share, principle component anaylisis, and cluster analysis.